The UK breakthrough cancer pain registry: origin, methods and preliminary data. (1st April 2011) - Ward, J; Laird, B; Fallon, M
Abstract : Abstract: Introduction and aims: Breakthrough cancer pain (BTcP) is a debilitating element of cancer pain. Rapidly absorbed formulations of fentanyl, such as fentanyl sublingual tablets (FST, Abstral, proStrakan, Galashiels, UK), are well matched to the rapid onset and short duration of BTcP episodes. Only limited data are available on the use of such agents outside clinical trials. The UK BTcP Registry was initiated to record patients' and clinicians' experiences of titration and treatment with FST. Methods: The UK BTcP Registry is an ongoing prospective, multi-centre programme. Any patient prescribed FST at a participating centre is eligible for inclusion. Patients and clinicians complete BTcP questionnaires at baseline and after successful titration or cessation of FST therapy; questions include disease history, analgesic use, pain response and medication preference. Questionnaire results are uploaded via a secure online system. The questionnaires and online system also provide clinicians with a method for ongoing monitoring of patients' experiences and outcomes. Results: To date, 33 patients have been recruited from 12 centres. In a preliminary analysis (n=31), patients experienced a mean of 4.9 BTcP episodes/day. 23/33 patients (70%) successfully titrated, and did so in a mean of 5.1 days; for 19/23 patients (83%), titration was easy/acceptable. Median pain relief was 70% with titrated FST, compared to 50% at baseline. 12/14 patients (86%) preferred FST to their previous medication. Conclusion: The UK BTcP Registry is a valuable developing resource, providing data on the effectiveness of FST (Abstral) outside of a clinical trial setting. It also provides a monitoring tool for front-line clinicians.